THE INFLUENCE OF BRAND IMAGE AND E-SERVICE QUALITY ON PURCHASE DECISIONS GENERATION Z AT E-COMMERCE SHOPEE IN PEKANBARU - Jusika, Alda; Afwa, Awliya; Puspita, Adella (Jurnal Apresiasi Ekonomi, 2024)
This research aims to analyze the Influence of Brand Image and E-Service Quality on Purchase Decisions of Generation Z at E-Commerce Shopee in Pekanbaru (Case Generation Z Pekanbaru). The object of this research is Generation Z in Pekanbaru City, with a sample of 100 respondents who are Shopee e-commerce users in Pekanbaru City. The data analysis technique uses Structural equation modeling using the Smart PLS version 3 application. The findings from this research show that Brand Image does not have a significant effect on purchase decisions at Shopee E-commerce in Pekanbaru city. Meanwhile, E-Service Quality has a positive and significant effect on Purchase Decisions. Based on the determination test, it is concluded that Brand Image and E-Service Quality influence Purchase Decisions on Shopee E-commerce simultaneously. Keywords:Brand Image, E-Service Quality, Purchase Decisions, E-commerce Shopee